Determination of Protein and Moisture in Fishmeal by Near-Infrared Reflectance Spectroscopy and Multivariate Regression Based on Partial Least Squares - Saeed Masoum (Iranian Journal of Chemistry & Chemical Engineering, 2012)
The potential of Near Infrared Reflectance Spectroscopy (NIRS) as a fast method to predict the Crude Protein (CP) and Moisture (M) content in fishmeal by scanning spectra between 1000 and 2500 nm using multivariate regression technique based on Partial Least Squares (PLS) was evaluated. The coefficient of determination in calibration (R2C) and Standard Error of Calibration (SEC) were 0.95 and 14.03 g / kg Dry Matter (DM) and 0.80 and 3.52 g / kg, for CP and M content, respectively. This study proved that the application of NIRS using PLS is well fitted to evaluate the protein and moisture content of fishmeal.